Understanding change management in organizational context: revisiting literature - Chowdhury, Anup; Shil, Nikhil Chandra (Management and Entrepreneurship: Trends of Development, 2022)
Every organization operates in dynamic and volatile environment and for this reason organizations should adopt the approaches to managing change. This conceptual study presents the tools for managing changes in the organization. The findings of this study offer a number of practical implications. It is expected to increase our understanding about the change management process in organizational context and this study will be of value to the academic researchers and practitioners. The study may be equally useful to the entrepreneurs who are engaged in initiating their new businesses. JEL Classification: D21, M10, M19, O33